2016
DOI: 10.1097/brs.0000000000001813
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Study Focused on Relief of Low Back Pain After Decompression Surgery in Selected Patients With Lumbar Spinal Stenosis Associated With Grade I Degenerative Spondylolisthesis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…A few different means of decompression surgeries were featured among the studies, with laminectomy and laminotomy being the most commonly performed. [14][15][16][17][18][19][20][21][22][23][24] One study assessed laminoplasty, 17 and 1 study assessed semi-circumferential decompression. 25 In 5 of the fusion studies, patients underwent un-instrumented posterolateral fusion, 15,17,21,22,26 and in the remaining fusion studies, some form of interbody fusion was used.…”
Section: Methodsmentioning
confidence: 99%
“…A few different means of decompression surgeries were featured among the studies, with laminectomy and laminotomy being the most commonly performed. [14][15][16][17][18][19][20][21][22][23][24] One study assessed laminoplasty, 17 and 1 study assessed semi-circumferential decompression. 25 In 5 of the fusion studies, patients underwent un-instrumented posterolateral fusion, 15,17,21,22,26 and in the remaining fusion studies, some form of interbody fusion was used.…”
Section: Methodsmentioning
confidence: 99%
“…A similar study documented patients' improvement in terms of physical progress [9]. Corresponding studies also show positive outcomes considering both the lower back pain and pain in the feet [10]. Previous studies further confirm that the patient's outcome after surgery is considered to be superior to conservative treatment [1].…”
Section: Introductionmentioning
confidence: 68%
“…[2][3][4][5] However, the mechanism causing LBP in LSS is not yet clear. 6 Although a few studies have shown improvements of LBP as well as leg symptoms by decompression surgery, [6][7][8] we have observed patients suffering for LBP after decompression surgery without fusion. Evidence suggesting that LBP in LSS is improved by decompression surgery is lacking, and the predicting factor for postoperative residual LBP is unknown.…”
Section: Introductionmentioning
confidence: 81%
“…Flat-back and limited lumbar mobility were shown to be risk factors for residual LBP. 8 Ikuta et al 7 reported that increased LL and SS, and decreased PT after decompression surgery were observed in their LBP improvement group. Additionally, other retrospective studies showed that preoperative and postoperative SVA values were correlated with LBP.…”
Section: Predictive Factor For Residual Lbpmentioning
confidence: 94%
See 1 more Smart Citation